Pengaruh Online Customer Review, Celebrity Endorser, Dan Brand Image Terhadap Keputusan Pembelian MS Glow Skincare Di Kota Malang - Laili, Jasilatul; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of Online Customer Review, Celebrity Endorser, and Brand Image on MS Glow Skincare Purchasing Decisions in Malang City. The sampling technique uses purposive sampling technique. This study uses explanatory research and a quantitative approach to obtain a sample of 100 respondents. The data collection method uses a questionnaire. To solve the problems in this study, using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, F tests, t tests, and determination coefficient tests. This study uses multiple linear regression analysis with the help of SPSS 25. The results of the study indicate that partially Online Customer Review, Celebrity Endorser, and Brand Image have a positive and significant effect on Purchasing Decisions. Keywords: Online Customer Review, Celebrity Endorser, Brand Image, Purchasing Decisions